Dyed in crimson : football, faith, and remaking Harvard's America - Eleff, Zev (Sport and society., 2023)
"In 1926, Harvard athletic director Bill Bingham chose former Crimson All-American Arnold Horween as coach of the university's moribund football team. The pair instilled a fresh culture, one based on merit rather than social status, and in the virtues of honor and courage over mere winning. Yet their success challenged entrenched ideas about who belonged at Harvard and, by extension, who deserved to lay claim to the American dream. Zev Eleff tells the story of two immigrants' sons shaped by a vision of an America that rewarded any person of virtue. As a player, the Chicago-born Horween had led Harvard to its 1920 Rose Bowl victory. As a coach, he faced intractable opposition from powerful East Coast alumni because of his values and midwestern, Jewish background. Eleff traces Bingham and Horween's careers as student-athletes and their campaign to wrest control of the football program from alumni. He also looks at how Horween undermined stereotypes of Jewish masculinity and dealt with the resurgent antisemitism of the 1920s"--